2021
DOI: 10.1002/star.202100094
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pectins with Different Structural and Conformational Characteristics on Gelatinization and Retrogradation of Corn Starch

Abstract: In this study, the effects of pectin with different structural and conformational characteristics on gelatinization and retrogradation of corn starch are investigated. The structural characteristics analysis showed that the low, medium, and high methoxyl pectin have different molecular weights (4.93×10 5 , 2.59×10 5 , and 3.26×10 5 Da), branched structures, and intrinsic viscosity (651.11, 641.99, and 1003.30 mL g −1 ). Pasting properties analysis results demonstrate that the presence of pectin retarded starch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The rheological properties, which demonstrate the relationship between the structural, mechanical and sensory properties, are among the basic parameters of pectin ( Xie et al, 2021 ). The rheological properties were measured using a Discovery HR-1 hybrid rheometer (TA Instruments, United States) with a cone-plate sensor.…”
Section: Methodsmentioning
confidence: 99%
“…The rheological properties, which demonstrate the relationship between the structural, mechanical and sensory properties, are among the basic parameters of pectin ( Xie et al, 2021 ). The rheological properties were measured using a Discovery HR-1 hybrid rheometer (TA Instruments, United States) with a cone-plate sensor.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, scholars have found that PEC could influence the gelatinization, retrogradation, and digestion properties of starch [11]. Xie et al [12] found that the presence of PEC significantly changed the viscoelasticity of corn starch gel (p < 0.05) and delayed the retrogradation of starch gel. Zhang et al [13] added PEC to corn starch and studied the effect of PEC molecular weight on retrogradation and digestion of starch.…”
Section: Introductionmentioning
confidence: 99%